Tuberculosis Infection Could Mimic Malignant Lymphoma In F-18 FDG PET: A Case Report - Ryan Yudistiro; Ivana Dewi Mulyanto; Febby Hutomo; Daniel Chung; Andree Kurniawan; Fajar L. Gultom; Ralph Girson Gunarsa (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Lymphoma and tuberculosis in several cases share similar clinical features that are difficult to differentiate. Lymphadenopathy, fever, malaise, weight loss, and respiratory symptoms are clinical features that could be found in both lymphoma and tuberculosis. Positron Emission Tomography/Computed Tomography Fluorodeoxyglucose (F-18 FDG PET) is a pivotal modality for imaging patients with cancer. Several non-malignant diseases like tuberculosis infection show high FDG uptake and lead to low specificity of F-18 FDG PET.Case Presentation: This case report describes a 55-year-old male patient with a history of Diffuse Large B-cell Lymphoma (DLBCL) who was suspected of having a recurrent disease. The patient has had a 6-month remission period after 6 cycles of R-CHOP regimen chemotherapy. He denied any known history of tuberculosis infection and HIV. F-18 FDG PET was performed to assess the extent of suspected lymphoma recurrent disease. F-18 FDG PET demonstrated multiple hypermetabolic bilateral neck region, mediastinum, and bilateral axilla lymphadenopathies. There were also multiple high FDG uptakes in the liver, mesocolon, and bones. The patient was suspected of having a lymphoma recurrent disease based on these findings. He underwent an excisional biopsy in the neck and was found to have lymphadenitis granulomatous disease from tuberculosis. Based on the histopathology finding, the patient received anti-tuberculosis drugs for 12 months and showed relief of signs and symptoms. F-18 FDG PET for anti-tuberculosis treatment evaluation revealed a complete metabolic response.Conclusion: Tuberculosis should be one of the differential diagnoses when a lymphoma recurrent disease is suspected. Clinical features, laboratory results, and imaging findings sometimes show similarities between lymphoma and tuberculosis. Histopathology evaluation is mandatory to confirm the diagnosis.